Racializar a notícia, pleiteando igualdade: a experiência da Imprensa Negra Contemporânea do Recife (1981-2002) - Carvalho, André Eduardo Bezerra de (2020)
Racializing the news, pleading for equality: the experience of the Contemporary Black Press of Recife (1981-2002) is inscribed in the studies that highlight the black protagonism and anti-racist struggle through alternative journalism in the contemporary history of Brazil and its Atlantic dialogues. This thesis aims to investigate the performance of five newspapers created by black entities from Pernambuco as an alternative to the small space reserved in the mainstream media for discussing racial issues. Angola, Negritude, NegrAção, Omnira and Djumbay are the titles that compose the analyzed sample. All of them came to light in the last two decades of the twentieth century and brought conflicting interpretations regarding the brazilian socio-racial structure advocated by dominant racial ideologies. Althought presenting quite different editorial focuses, they converged on the combat of racism and the search for full recognition of the black population in the democratic structure of the New Brazilian Republic that was outlined after years of military dictatorship. Thusly, they exhibited multifaceted strategies to unveil brazilian racism and demand policies that recognized the black person in society far from the spectrum of the universalist and assimilationist discourse.